A novel and apparent de novo ALAS2 missense variant associated with congenital sideroblastic anemia - Jianling Cai; Tianming Liu; Yuxuan Huang; Hongxing Chen; Meidie Yu; Dongqing Zhang; Zhanqin Huang (Frontiers Media S.A., 2024)
BackgroundCongenital sideroblastic anemia (CSA) constitutes a group of inherited erythropoietic disorders. Some affect mainly or exclusively erythroid cells; other syndromic forms occur within multisystem disorders with extensive nonhematopoietic manifestations. In this study, we have performed clinical and molecular investigations on a 10-year-old boy suspected of having CSA.MethodsRoutine blood examination, peripheral blood and bone marrow smears, and serum iron tests were performed. Gene mutation analysis was conducted using whole-exome sequencing (WES) and the results were confirmed using Sanger sequencing. Furthermore, the functional impact of the identified variant was assessed/predicted with bioinformatics methods.ResultsThe patient presented with severe microcytic anemia (hemoglobin, 50 g/L), iron overload and ring sideroblasts in the bone marrow. Moreover, WES revealed the presence of a hemizygous missense variant in ALAS2 (c.1102C > T), changing an encoded arginine to tryptophan (p. Arg368Trp). This variant was verified via Sanger sequencing, and neither of the parents carried this variant, which was suspected to be a de novo variant. Using in silico analysis with four different software programs, the variant was predicted to be harmful. PyMol and LigPlot software showed that the p. Arg368Trp variant may result in changes in hydrogen bonds. The patient was treated with vitamin B6 combined with deferasirox. After 6 months, the hemoglobin increased to 99 g/L and the serum ferritin decreased significantly.ConclusionWe report a novel pathogenic variant in the ALAS2 gene (c.1102C > T:p. Arg368Trp), which caused CSA in a 10-year-old boy. Mutational analysis is important in patients with CSA when family history data are unavailable. Anemia due to the ALAS2 Arg368Trp variant responds to pyridoxine supplements.